ANALISIS WACANA IKLAN AIR MINUM DALAM KEMASAN (AMDK) PADA KANAL YOUTUBE SEHATAQUA DAN LE MINERALE: TELAAH STRUKTUR DAN FUNGSI BAHASA - Ekawati, Mursia; Qodri Rinjani , Afifah; Eka Pradita, Linda (UNIVERSITAS PGRI YOGYAKARTA, 2024)
The purpose of this study is to describe the advertising discourse of two brands of bottled drinking water (AMDK), namely the AQUA and Le Minerale brands on the YouTube channel. It becomes an interesting conversation when the two water brand advertisements favor each other's positive image and seem to give hidden messages in the language used. The analysis method uses Van Dijk's critical discourse analysis perspective and formalist language functions. Based on the results of the analysis found on the use of language displayed in the two discourses of mineral water product advertisements, it forms a different construct. This is caused by several aspects. Standardized variety is widely used in Le Minerale advertising discourse while non-standardized variety is widely used in AQUA advertising discourse. The emergence of contraction patterns in the production of words chosen by mineral water brands but there are many affixation processes in the choice of words in Le Minerale's advertising discourse. There are differences in delivering the introduction in opening an advertising discourse between Le Minerale and AQUA products.